2011
DOI: 10.3103/s1062873811110190
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative processes in peripheral heavy ion collisions at Fermi energies

Abstract: Heavy ion collisions in the Fermi energy regime may simultaneously show features of direct and dissipative processes. To investigate this behavior in detail, we study isotope and velocity distributions of projectile-like fragments in the reactions 18 O (35MeV/A) + 9 Be( 181 Ta) at forward angles. We decompose the experimental velocity distributions empirically into two contributions: a direct, 'breakup' component centered at beam velocity and a dissipative component at lower velocities leading to a tail of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The de-excitation of primary fragments moves the spectra to the light mass region. It has been investigated that the peripheral nucleus-nucleus collisions have the advantage for creating the neutron-rich isotopes [26]. Shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The de-excitation of primary fragments moves the spectra to the light mass region. It has been investigated that the peripheral nucleus-nucleus collisions have the advantage for creating the neutron-rich isotopes [26]. Shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The de-excitation of the primary fragments moves the spectra to the light mass region. It has been found that the peripheral nucleus-nucleus collisions have the advantage of creating neutron-rich isotopes [31]. Figure 4 shows a comparison of the effects of the different symmetry energies on the fragment distribution in the symmetric reaction of 136 Xe+ 136 Xe at an incident energy of 20 MeV/nucleon, with the impact parameters of 8-10 fm.…”
Section: Resultsmentioning
confidence: 99%